Derangement of PaCO2 requires physician attention in acute carbon monoxide poisoning. (May 2020) - Moon, JM; Chun, BJ; Cho, YS
The objective was to describe the prevalence of derangement of the partial pressure of arterial carbon dioxide (PaCO2 ) and to determine the association between PaCO2 and adverse cardiovascular events (ACVEs) in carbon monoxide (CO)-poisoned patients. Additionally, we evaluated whether the derangement of PaCO2 was simply secondary to metabolic changes. This retrospective study included 194 self-breathing patients after CO poisoning with an indication for hyperbaric oxygen therapy and available arterial blood gas analysis at presentation and 6 h later. The incidence rate of hypocapnia at presentation after acute CO poisoning was 67.5%, and the mean PaCO2 during the first 6 h was 33 (31–36.7) mmHg. The most common acid–base imbalance in 131 patients with hypocapnia was primary respiratory alkalosis. The incidence rate of ACVEs during hospitalization was 50.5%. A significant linear trend in the incidence of ACVEs was observed across the total range of PaCO2 variables. In multivariate regression analysis, mean PaCO2 was independently associated with ACVEs (odds ratio 0.051; 95% confidence interval 0.004–0.632). PaCO2 derangements were common after acute CO poisoning and were not explainable as a mere secondary response to metabolic changes. The mean PaCO2 during the first 6 h was associated with ACVEs. Given the high incidence of ACVEs and PaCO2 derangement and the observed association between the mean PaCO2 and ACVEs, this study suggests that (1) PaCO2 should be monitored in the acute stage to predict and/or prevent ACVEs and (2) further investigation is needed to validate this result and explore the early manipulation of PaCO2 as a treatment strategy.